Association of Atraumatic Splenic Rupture and Acute Pancreatitis: Case Report with Literature Review. (14th February 2022) - Ljubicic, Lidija; Sesa, Vibor; Cukovic-Cavka, Silvija; Romic, Ivan; Petrovic, Igor
Abstract : Atraumatic splenic rupture is an uncommon complication of acute pancreatitis. This article presents a case of a 35-year-old patient presenting with acute pancreatitis who subsequently developed a splenic vein thrombosis and splenic rupture requiring a laparotomy and splenectomy. This rare but life-threatening complication requires prompt recognition and management in patients with pancreatitis who develop sudden hemodynamic instability.